Governing by campaigning the politics of the Bush presidency. - Edwards, George C (Great questions in politics series., 2007)
This brief text, by one of the foremost experts on the presidency, explores how the Bush administration has attempted sweeping changes in public policy - without broad support for doing so - by taking its case to the American public more than any other president in history.--BOOK JACKET.